The effect of feet placement during the wall contact phase on freestyle turns - Cossor, J.; Slawson, S.; Conway, P.; West, A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
A waterproofed pressure mat was used to analyse the wall contact phase of freestyle turns by 34 university swimmers to determine the variables on the wall that effect turning performance. Data was analysed as a group of athletes and then divided by gender to see if males and females used the same approach to turning technique with different anthropometry. Foot position and orientation with relation to the surface of the water, wall contact time and maximum depth were related to the criterion measure of Sm Round Trip Time (RTI). Within the group that was tested the only significant correlation (p=O.OS) with turn performance during the wall contact phase was the tuck index (0.330). When the sample was divided by the gender of the swimmer the foot width and orientation were significantly related to the Sm RTI for the males while the Wall Contact Time (WCT). foot height, foot width and tuck index were related to female turn performance. Rotation time, height, mass and tuck index were related with successful turning while future testing should investigate the turning performance freestyle specialist swimmers to determine the impact of foot placement.